2004
DOI: 10.1081/cbi-120039814
|View full text |Cite
|
Sign up to set email alerts
|

Chronotoxicity of Nedaplatin in Rats

Abstract: Chronotoxicologic profiles of nedaplatin, a platinum compound, were evaluated in rats maintained under a 12 light/12 dark cycle with light from 07:00h to 19:00 h. Nedaplatin (5 mg/kg) was injected intravenously, once a week for 5 weeks at 08:00h or 20:00h. The suppression of body weight gain and reduction of creatinine clearance were significantly greater with the 20:00h than 08:00h treatment. Accumulation of nedaplatin in the renal cortex and bone marrow were also greater with 20:00 h treatment. There were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In contrast, nocturnally active rats as well as night shift workers were apparently little affected (Brelis, 1984). Circadian rhythmicity in host tolerance to, and toxicity of, chemical agents was first documented in laboratory experiments almost 50 yrs ago; more recent examples include ketamine/midazolam (Rebuelto et al, 2005), nedaplatin (Cui et al, 2004), irinotecan (Filipski et al, 2004), alcohol (Danel and Touitou, 2004), loratadine (Dridi et al, 2005), and morphine (Cui et al, 2005). The hypothesis of the MIC chronotoxic effect, however, has never been tested.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, nocturnally active rats as well as night shift workers were apparently little affected (Brelis, 1984). Circadian rhythmicity in host tolerance to, and toxicity of, chemical agents was first documented in laboratory experiments almost 50 yrs ago; more recent examples include ketamine/midazolam (Rebuelto et al, 2005), nedaplatin (Cui et al, 2004), irinotecan (Filipski et al, 2004), alcohol (Danel and Touitou, 2004), loratadine (Dridi et al, 2005), and morphine (Cui et al, 2005). The hypothesis of the MIC chronotoxic effect, however, has never been tested.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, Cui et al have demonstrated that a correlation is detected between content of platinum in the renal cortex and nephrotoxicity induced by nedaplatin. 19) However, there is no report of the relationship accumulation of cisplatin and nedaplatin in the kidney to their nephtoroxicity.…”
Section: -7)mentioning
confidence: 99%
“…This has been demonstrated by a large number of chronotoxicology modeling experiments done on laboratory animals as well as clinical studies conducted on male and female cancer patients. [35][36][37][38][39][40] It is of interest that the initial clinical chronotoxicology trial of cancer medications was done on women 20 years ago by Hrushesky. 35 The purpose of this groundbreaking research was to determine if the toxicity of the first-line cancer medications, doxorubicin and cisplatin, used to treat bladder and gynecological malignancies could be significantly attenuated by infusing them to circadian rhythms.…”
Section: Smolensky Et Al 40mentioning
confidence: 99%